Developing Activity Model of Tuberculosis Patient Care in Psychiatric Patients Group at Ban Metta Home for Destitute Nakhon Ratchasima Province - Chumchit, Pattareeya; Parisai, Vajirapol; Mungomklang, Anek; นิยมปัทมะ อนุชิต (Journal of Health Science of Thailand, 2017)
Community Medical Unit 3 (Wat Bun) is located in the area of Nakhon Ratchasima City Municipality. Operations on continuous prevention and control of communicable diseases were hindered by problems on persistence of epidemics. Therefore, CMU 3 conducted systematic epidemiological review and putting in place, especially related activity models of tuberculosis patient care, at Ban Metta Home of Destitute, Nakhon Ratchasima Province. Patients were 496 disadvantaged, mental disabled and wandering persons whom 80.04 percent of them were schizophrenics. Activities of patient care were suitably provided for any condition by developing a mobile model of tuberculosis patient care, adoping Directly Observed Treatment Short - course (DOTS) to observe patients in drug taking through 180 days, producing motivation on having drugs by supporting with milk and desserts in order to deter them from keeping drugs in their mouth and later spitting out. This study was aimed at evaluation of the activity model development. Study design was descriptive study in form of a model development by specific activities for tuberculosis patient care in such group, with P-D-C-A cycle and persented in percentage. Three dead cases of tuberculosis, led to target groups screening of 397 persons in the premise. Chest x-ray identified abnormalities films matched with invasive period of tuberculosis infection in 6 patients accounted for 1.51 percent. Phlegm could not be collected due to un-cooperating nature of the patients, The study was conducted between October 1, 2010 and April 30, 2011. Data were reviewed for creating a guideline for tuberculosis patient care in psychiatric patients group. Reviewing of activities on tuberculosis patient care in psychiatric patients group led to a guideline of DOTS protocol in these psychiatric patients with success and patients were completely treated. Activities for preventing disease transmission were conducted by separation of sleeping quaters especially through 14 highly contagious days and over 180 consecutive days of treatment and screening measures for new comers of homes of destitute. If such model were adopted for tuberculosis patient care in psychiatric patient group in other 11 homes for destitute in Thailand, it would reduce disease transmission and prevent drugs resistance in psychiatric patient group which had problems on taking drugs.